Konservasi In Vitro Pamelo (Citrus maxima (Burm.) Merr.) melalui Pertumbuhan Lambat - Tyas, Kartika Ning; Susanto, Slamet; Dewi, Iswari Saraswati; Khumaida, Nurul (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
Indonesia is one of the countries which have abundant germplasm of pummelo (Citrus maxima (Burm.) Merr.). Thepummelo germplasm must be conserved to prevent its extinction due to biotic and abiotic stresses. In vitro conservationusing slow growth technique can be considered as an alternative of ex-situ conservation. Two experiments were conductedto obtain suitable medium to conserve pummelo in vitro. The first experiment was conservation using modified concentrationof MS and sucrose. MS medium concentrations were 1/2MS and MS, while sucrose concentrations were 0, 1, 2 and 3%. Thesecond experiment was conservation using osmoticum and retardant in MS medium. There were six combinations of MSmedium supplemented with osmoticum and retardant, i.e. MS + sucrose 3%, MS + sucrose 3% + paclobutrazol 7.5 ppm, MS+ sucrose 3% + paclobutrazol 15 ppm, MS + sorbitol 2%, MS + sorbitol 2% + paclobutrazol 7.5 ppm, MS + sorbitol 2% +paclobutrazol 15 ppm. The results showed that reducing MS medium and sucrose consentration decreased leaf number andshoot length but increased root number and length. The combination of osmoticum and retardant reduced shoot length, leaf number, root number and length. Based on the planlet visual and inhibition of growth through the decrease of leaf number, shoot and root length, the best medium to preserve pummelo was MS + sorbitol 2% + paclobutrazol 7.5 ppm.Keywords: Citrus maxima, osmoticum, preservation, retardant, slow growth